Large saphenous venous graft aneurysm mimicking atypical mediastinal mass - Krotin Mirjana; Ristić Miljko; Zdravković Marija; Popović-Lisulov Danica; Saponjski Jovica; Putnik Svetomir (Vojnosanitetski Pregled)
Background. Saphenous venous graft (SVG) aneurysm is a very rare but potentially fatal complication of the coronary artery bypass surgery. Case report. We reported a case of 72-year-old man admitted to hospital because of atypical chest pain related to body motions in horizontal position, especially to the left side. Pain was followed by dispnea, palpitations, fatigue, cough, yellow sputum expectorations, as well as elevated temperature. He had had coronary artery bypass grafting (CABG) surgery with saphenous vein grafts (SVGs) to the left anterior descending artery (LAD) and right coronary artery (RCA) 27 years earlier. Chest X-ray revealed a poor-defined shadow in the region of the right atrium. A transthoracic echocardiogram revealed an atypical tumorous mediastinal mass near the right atrium and right ventricle that seemed partially calcified on transesophaeal echocardiography (TEE). CT scan confirmed an atypical mediastinal mass in contact with the right ventricle that might be a right ventricle aneurysm, pericardial cyst or SVG aneurysm. Coronary angiography was performed subsequently and it revealed a big saphenous venous graft aneurysm originating from the previous venous graft to the RCA. The aneurysm was resected and a new bypass graft was placed. Histopathology confirmed a true aneurysm of the venous graft. Conclusion. Although SVG aneurysm is a very rare complication of CABG surgery, patients presenting with atypical hilar or mediastinal mass following CABG should always be evaluated firstly for existence of this cardiosurgical complication.